Patient‐reported outcome measures (PROMs) of implant‐supported reconstructions using digital workflows: A systematic review and meta‐analysis. (12th October 2021) - Bishti, Shaza; Tuna, Taskin; Rittich, Anne; Wolfart, Stefan
Abstract: Objectives: To summarize the existing evidence on patient‐reported outcome measures (PROMs) of implant‐supported restorations fabricated using a digital workflow in comparison to conventional manufacturing procedures. Methods: A PICO strategy was executed using an electronic and manual search focusing on clinical studies evaluating PROMs of implant‐supported restorations. Only clinical trials assessing conventional versus digital workflows for implant‐supported restorations were included. PROMS on implant impression procedures and fabrication of final restorations were evaluated using random and fixed effects meta‐analyses, while implant planning/placement was reported descriptively. Results: Among 1062 titles identified, 14 studies were finally included, and only seven studies were eligible for meta‐analysis. For implant planning and placement, only a qualitative analysis was possible due to heterogeneity between the studies. For impression procedures, the random effects model revealed statistically significant differences in taste, anxiety, nausea, pain, shortness of breath, and discomfort in favor of optical impressions. No significant difference in the subjective perception of the duration of an impression could be reported. For the final fabrication of restorations, no significant difference between veneered and monolithic posterior restorations was found in terms of esthetic, function, and general satisfaction. Conclusion: Most of the studies reporting about PROMs were published during the last ten years and limited to implant‐supported single crowns in the posterior region. Based on PROMs, no scientifically proven recommendation for guided implant placement could be given at this time. Patients showed high preference for optical impressions, whereas no differences between veneered and monolithic restorations could be reported.